Pengaturan Pidana Pembuatan Meme Vidio menggunakan Teknologi Artificial Intelegence di Media Sosial Perspektif Peraturan Perundang-Undangan di Indonesia - Hidayat, Faisal; Hafrida; Erwin (AL-SULTHANIYAH, 2026)
The development of Artificial Intelligence (AI) technology has enabled the creation of increasingly realistic digital memes and videos that are easily disseminated through social media. This presents new challenges in criminal law enforcement, particularly when the AI content contains violations such as defamation, identity manipulation, privacy violations, and disinformation. This study aims to answer two research questions: (1) how criminal law in Indonesia regulates the creation and distribution of AI-based video memes on social media; and (2) what form of criminal liability is imposed on creators of AI-based video memes that contain elements of legal violations. This study uses a normative legal research method, positioning law as a system of norms examined through literature review. The approaches used include a statutory regulatory approach, a case approach, a contextual approach, and a comparative approach. The legal sources consist of primary legal materials in the form of the Criminal Code, the New Criminal Code, the Electronic Information and Transactions Law, the 1945 Constitution, and other related regulations; secondary legal materials in the form of books, legal journals, and expert opinions; and tertiary legal materials such as legal dictionaries and encyclopedias. The research findings indicate that current Indonesian legal regulations do not specifically regulate the creation of AI-based memes or videos. Therefore, law enforcement still relies on general provisions such as Articles 27–36 of the Electronic Information and Transactions Law (ITE Law) and articles of the Criminal Code concerning defamation, insults, or the dissemination of unlawful content. Consequently, there are limitations in norms and disclosures in determining the elements of culpability and accountability of AI content creators. Therefore, this research emphasizes the need for reform of national criminal law, both through specific regulations regarding AI-based content and by strengthening the concept of criminal liability in the context of generative technology.